Computational model for the acylation step of the β-lactam ring: Potential application for l,d-transpeptidase 2 in mycobacterium tuberculosis - Fakhar, Zeynab; Govender, Thavendran; Lamichhane, Gyanu; Maguire, Glenn E.M.; Kruger, Hendrik G.; Honarparvar, Bahareh (Journal of molecular structure, 2017)
Tuberculosis (TB) remains a major global health quandary. The peptidoglycan layer of mycobacterium tuberculosis (M.tb) consists of glycoproteins that are crosslinked by transpeptidases. Carbapenems are a subfamily of β-lactam antibiotics that inactivate the L,D-transpeptidase enzyme effectively (3 → 3 crosslinks). The mechanism of ring opening and thioester bond formation between the β-lactam core and the Cys354 active residue (for L,D-transpeptidase) during the acylation step is still the subject of considerable discussion. Herein, an acylation mechanism is proposed through four possible model transition states (TS), namely four membered-ring (TS-4, TS-4-His and TS-4-water) and six membered-ring (TS-6-water) transition states. The quantum chemical calculations for these TS models were performed with Density Functional Theory (DFT) using the B3LYP functional and the 6-31 + G(d) basis set. The calculated thermodynamic properties such as relative reaction energies (ΔEreaction), Gibbs free energies (ΔG), enthalpy energies (ΔH) and entropy contributions (ΔS) were reported at 298.15 K for the four considered pathways. The highest occupied molecular orbital (HOMO) and the lowest unoccupied molecular orbital (LUMO) were calculated to evaluate and compare the chemical reactivities of the considered TS models. Natural bond orbital (NBO) analysis was performed to determine the effective intermolecular orbital interactions E(2) derived by the second perturbation theory. The chemical hardness (η) and softness (S) and Fukui indices (fk+, fk−) of these TS models were compared to confirm the feasibility and preference of the considered pathways. The outcome of this study will pave the way for an improved understanding of the LDT/carbapenem acylation reaction at a molecular level. [Display omitted] •The inhibition mechanism of a model Beta-lactam ring against L,D-transpeptidase of Mycobacterium tuberculosis is proposed.•From the four proposed models, six-membered ring TS model in presence water molecule is found to be preferred.•The catalytic role of water in facilitating a concerted proton transfer process is justified.